Two Visualization Tools for Analyzing Agent-Based Simulations in Political Science. - Chang, Remco.; Crouser, R. Jordan.; Kee, Daniel E.; Jeong, Dong Hyun. (Tufts University. Tisch Library., 2017)
Agent-based modeling has become a key technique for modeling and simulating dynamic, complicated behaviors in the social and political sciences. Although many robust toolkits for developing and running these simulations exist, systems that support analysis of their results are few and tend to be overly general. So, social scientists have had difficulty interpreting the results of their increasingly complex simulations. To help bridge this gap between data generation and interpretation, researchers collaborated with political science analysts to design two tools for interactive data exploration and domain-specific data analysis. Testing by the analysts validated that these tools provided an efficient framework to explore individual trajectories and the relationships between variables. The tools also supported hypothesis generation by enabling analysts to group simulations according to multidimensional similarity and drill down to investigate further. © 2012 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.